A review of 263 years of taxonomic research on Hypoplectrus (Perciformes: Serranidae), with a redescription of Hypoplectrus affinis (Poey, 1861) - Puebla, Oscar; Coulmance, Floriane; Estapé, Carlos J.; Estapé, Allison Morgan; Robertson, D. Ross (Zootaxa, 2022)
The hamlets (Hypoplectrus spp., Perciformes: Serranidae) constitute a distinctive model system for the study of a variety of ecological and evolutionary processes including the evolution and maintenance of simultaneous hermaphroditism and egg trading, sex allocation, sexual selection, social-trap, mimicry, dispersal, speciation, and adaptive radiation. Addressing such fundamental and complex processes requires a good knowledge of the taxonomy and natural history of the hamlets. Here, we review the taxonomy of the hamlets, from early ichthyological studies to the most recent species description in 2018. We report a total of 72 different binomial names for Hypoplectrus, synonymized or invalidated down to 17 unambiguously recognized species today. In addition, we redescribe Hypoplectrus affinis (Poey, 1861) as a valid species. In Bocas del Toro (Panama), this hamlet is distinct from eight sympatric congeners in terms of colour pattern, body size and behaviour. Whole-genome analysis and spawning observations indicate that it is genetically distinct from sympatric congeners and reproductively isolated through assortative pairing. Based on the colour pattern we detail in its redescription, live-fish photographs, videos, and earlier reports, H. affinis occurs in Panama, Nicaragua, Mexico, the Florida Keys, Cuba, Grand Cayman, Jamaica, the Dominican Republic, Los Roques (Venezuela), Bonaire, and Tobago. We conclude with a discussion of pending taxonomic issues in this group and the species status of the hamlets in general.